Analysis of Foundation Application Results Using Airbrush on Combination Facial Skin Types - Israwati Hamsar (JURNAL PAKARENA, 2023)
This research is a descriptive study that aims to find out the results of applying foundation using an airbrush on combination facial skin types. The number of respondents in this study was 20 trained panelists. Data collection techniques used were observation, Focus Group Discussion (FGD), documentation, questionnaires, and interviews. The data analysis technique used is descriptive and Likert scale. The results of this study indicate that with the application of foundation using an airbrush on combination facial skin, the evenness of the foundation is considered to be able to cover pores and acne scars, but the selection of the foundation color shade is not quite right so the skin color looks uneven. The durability of the foundation is considered to be able to last when left for 2 hours. Based on the opinion of the panelists regarding the results of applying airbrush, it is in the very good category at 85%. And in the aspect of resilience assessment, namely 98.75%.